Performance analysis of the GraphQL API creation technologies using Spring Boot and NestJS - Tkaczyk, Jakub Maciej; Pańczyk, Beata (Journal of Computer Sciences Institute, 2025)
Multitude of requirements for internet applications has led to creation of countless technologies. Goal of this article is to compare performance of server-side applications providing GraphQL API. Using frameworks NestJS and Spring Boot applications with the same business logic were created. Applications utilize the same data source - database "airport" developed for the experiment. In order to verify formulated hypotheses stress test was conducted. Each test set consisted of following number of requests: 1000, 2000, 4000. Tests showed that NestJS performance exceeds Spring Boot in GraphQL queries. However, GraphQL mutation results point out opposite.